Minimasi Biaya Pengadaan Barang Pada Soraya Wedding Menggunakan Aplikasi Anylogic - Rahmadhani, Wulan; Rafly Vardian, Rezky; Batara Simangungsong, Tumpak (CV RIFAINSTITUT, 2023)
The Wedding Organizer at the Soraya Wedding company explained that the problem that is often encountered in the implementation of weddings is the large costs that must be incurred to pay for goods to vendors or providers of goods. This situation results in Soraya Wedding having difficulty in finding customers to use its services, because the price set must be higher than the expenditure. The research was conducted by comparing several scenarios from existing data. Then the scenario that has been prepared is applied to AnyLogic software. The scenarios used are 3 (three), including the number of workers (decoration, catering, complementary equipment), the level of costs (worker salaries, transportation, vendor profits, Soraya Wedding profits), and down payments (vendors and Soraya Wedding). The results of simulations that have been carried out using the AnyLogic application are obtained for scenario 1, namely the price for customers of Rp.21,086,653 with preparation for implementation for 16 days. In scenario 2 it amounted to Rp.12,264,208 with preparation for implementation for 26 days. Furthermore, scenario 3 amounted to Rp.14,126,449 with preparation for implementation for 17 days. Based on the data processing that has been done, the way to make the costs incurred lower in the procurement of goods for the implementation of weddings using Soraya Wedding services is to cut the number of workers involved in the procurement of goods, if it is difficult to cut the number of workers, it can be done by reducing the salary level for workers in order to minimize the costs incurred, as well as efficiency and effectiveness in the use of transportation in order to reduce the level of transportation costs to minimize costs incurred.